Prognostic Significance of Sarcomatoid Differentiation in Patients With Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Zhi, Hong; Feng, Meiling; Liu, Suo; Na, Ta; Zhang, Nandong; BiLiGe, WuEn (Frontiers in Oncology, 2020)
Background: To date, the prognostic value of sarcomatoid differentiation in patients having metastatic renal cell carcinoma (mRCC) remains inconclusive. A systematic review and meta-analysis were conducted. Materials and Methods: Relevant literatures were obtained from PubMed, Embase, and Cochrane Library published prior to May, 2020. All patients were diagnosed with mRCC and treated with surgery, cytokine therapy, targeted therapy, immunotherapy. Sarcomatoid differentiation in the pathological specimens was identified. Each endpoint (overall survival [OS], progression-free survival [PFS], and cancer-specific survival [CSS]) was assessed using a multivariable adjusted hazard ratio (HRs) and 95% confidence interval (CIs). Results: Fifteen observational studies having 5828 patients with mRCC were included. The merged results showed that patients presenting sarcomatoid differentiation had a significantly inferior OS (HR: 2.26, 95% CI: 1.82-2.81; P < 0.001), PFS (HR: 2.28, 95% CI: 1.63-3.19; P < 0.001), and CSS (HR: 2.27, 95% CI: 1.51-3.40; P < 0.001) compared to those without sarcomatoid differentiation. Subgroup analysis based on publication year, patient population, country, number of cases, and NOS score did not change the direction of results. A significant publication bias was identified for OS, but no publication bias was identified for PFS. Moreover, sensitivity analysis also verified the robustness of the results. Conclusion: This study suggested that sarcomatoid differentiation was correlated to unfavorable clinical outcomes in mRCC and may be a poor prognostic factor incorporating to prognostic models for mRCC patients.